The Information as a resource in building knowledge for the Supplies and Warehouse area: A case study in the plastic packaging industry - Cavallari Filho, Roberto; Rocha Ribeiro, Karla Cristina [UNESP]; Bitencourt Jorge, Carlos Francisco [UNESP]; Cazane, Ana Livia [UNESP]; Domingues, Vinicius Nascimento (Univ Federal Santa Catarina, 2020)
Objective: The Information is currently one of the main strategic resources for companies and needs to be well managed. In this article, this premise is taken seriously in the application of a research on information as a strategic resource for the construction of knowledge aiming to analyze the subjects' perception of the information and accumulated knowledge related to the activities in the Supply and Warehouse department of an industry packaging producer in the state of Sao Paulo. Method: The research was based on the dynamic method of Case study to guide the collection of research data from the application of questionnaires, interviews and observation in order to identify the perception of the subjects regarding the information and knowledge of that department. To theoretically base the research, a historical rescue of the evolution of resource management was used as a strategic tool in the management of the supply chain and warehouse, as well as an analysis of information as a strategic resource for the construction of knowledge. Results: Thus, when presenting, analyzing and interpreting the research data, the perception of the research subjects is quantified and qualified about the importance of an organizational culture of valuing and strengthening the information flow between the activities of the department, whether of direct or indirect way. Conclusions: We note the need to build an informational culture among the subjects that make up the department, as well as the development of informational competence in the subjects that make up the industry. Among the vestments suggested aiming to enhance the use of information in the context of knowledge construction, the adoption of an information management model, as well as of Information and Communication Technologies (ICTs) that provide the centralization of the information prospected in the internal and external environment in a single database.
Keywords: Competitive strategy; Information management; Knowledge; Supply and warehouse management; Plastic packaging company